Metacognição: um apoio ao processo de ensino e aprendizagem na banda de música - Gonçalves, Cristiane Soares (2023)
This abstract is about the presentation of a doctoral thesis linked to the Graduate Program of the Federal University of Ceará - UFC on research related to music education in symphonics bands, within the axis of Music Teaching in the Line of Research, Education, Curriculum and Education - LECE. The research, qualitative and exploratory in nature, verified the scope and possibilities of metacognitive strategies in the process of teaching and learning instrumental practice and in the formation of repertoire of symphonics bands. The studies proposed to carry out this thesis were organized within the scope of investigations into metacognition initiated by John Hurley Flavell, in the 1970s; the development of metacognitive aspects in Lafortune, Jacob and Hébert (2003) and Pallascio, Daniel and Lafortune (2004), referring to studies on the development of musical skills by Dubé and Garcia (2014), as well as research on the production of products based in Simon (1996), with Design Science, and Lacerda et al. (2013) in Design Science Research, among others. Furthermore, for data analysis, the research was based on studies referring to Heidegger's (2015) phenomenology on consciousness; Van Manem (2014, 2016) regarding lived experience and Husserl (2000), regarding the existence of being. The research methodology was structured based on the Design Science Reserch methodological approach, addressing a qualitative approach in the preparation of the “Didactic notebook of metacognitive strategies of Metacognitive Strategies for Symphonics Bands (CADEM )” and the continued formation of symphonics bands conductors to use metacognition in their praxis, linking application of the COMÉGAN survey (Metacognitive Knowledge and Management of Mental Activities) and reflection sheets to those involved for analysis and verification of data with the experiment. Fifteen conductors from different regions of Brazil participated in the research and of the course through virtual classes and activities on metacognition, applying the knowledge acquired in their respective bands through the use of CADEM. The results of the entire research experience with metacognition provided evidence of improvement in musicians' musical performance in repertoire formation with increased metacognitive knowledge about strategies and management of mental planning activities. The CADEM demonstrated a construct favorable to pedagogical support for bands conductors, improving their teaching potential and promoting the development of critical awareness between conductors and musicians in a relevant and meaningful way within the musical teaching and learning process.